PENANAMAN KARAKTER PEDULI SOSIAL MELALUI PEMBELAJARAN BERCERITA PADA ANAK USIA 5-6 TAHUN DI RA. IRBAH GOLDEN AGE SURABAYA - Puput Yulianti; Irfai Fathurohman; Mohammad Kanzunnudin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2022)
This study aims to describe the cultivation of socially caring characters through storytelling learning in children aged 5-6 years in RA. Irbah Golden Age Surabaya. Researchers photographed the course of storytelling experienced by teachers and children in RA. Irbah Golden Age Surabaya translated into words. Researchers also describe social caring characters that appear after children listen to stories. The subjects in this study were children aged 5-6 years in RA. Irbah Golden Age Surabaya for the 2022-2023 school year. Number of subjects 20 children aged 5 - 6 years. Sources of data in this study were obtained through observation of researchers in learning to tell stories during 5 meetings. The results showed that storytelling at this institution was carried out well from opening to closing for 5 consecutive days. The results showed that after learning to tell stories, 75% of children like to share and can speak politely. 14 children or 70% of the subjects stated that after listening to stories they were able to love their friends. 70% of the subjects stated that after listening to the story they did not force their will, were able to queue, were able to train their emotions by showing an attitude that could be felt, namely not getting angry when they found something inappropriate. according to their wishes. From the results of this study the researchers concluded that learning to tell stories proved to be a strategy for instilling socially caring character education in children aged 5-6 years in RA. Irbah Golden Age Surabaya.